EFFICIENCY OF USING INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Conference Zone, 2023)
The article presents the projecting lesson on the basis of pedagogical technology. Pedagogical technology is aimed at solving the intended and intended goal of the educational process.